A new type of phosphaferrocene–pyrrole–phosphaferrocene P-N-P pincer ligand - Tian, Rongqiang (2013)
A 2-ethoxycarbonylphosphaferrocene was reduced to the corresponding 2-hydroxymethyl derivative, which was condensed with pyrrole in a 2:1 ratio in the presence of BF3 to give a phosphaferrocene–pyrrole–phosphaferrocene pincer ligand. This tridentate ligand, in turn, reacted with [Rh(acac)(CO)2] to yield a rhodium carbonyl pincer complex. This complex was characterized by X-ray crystal structure analysis and tested in the hydroformylation of internal olefins.